Optimization of ultrasound-assisted extraction of herbicides from soil and rice using Response surface modelling. Issue 1 (2nd January 2023) - Kaur, Pervinder; Kaur, Harshdeep; Kaur Kalsi, Navroop; Bhullar, Makhan Singh
ABSTRACT: A simple, efficient and cost-effective ultrasound-assisted extraction method for the quantification of penoxsulam, anilofos, bispyribac sodium, butachlor and pretilachlor from soil and rice was developed and validated. Three independent variables, including ultrasonication temperature, ultrasonication time, type and volume of solvent, were studied by single-factor experiments. Box–Behnken design (BBD) was also used to determine the optimal parameters for efficient extraction of penoxsulam, anilofos, bispyribac sodium, butachlor and pretilachlor herbicides from soil and rice. Under optimum conditions, the mean percent recoveries ranged from 82.1 ± 3.32 to 93.8 ± 2.56 from soil and rice grain with relative standard deviation <10% and limit of quantification less than the maximum residue limits imposed by principal regulatory agencies. Results depicted that the experimental values were consistent with the predicted values, indicating that RSM is accurate and reliable method to find the optimal UAE extraction conditions for studied herbicides from soil and rice. Furthermore, the greenness was evaluated using AGREE metrics, and UAE was found to be a greener and efficient method for the determination of herbicides from soil and rice. The developed method was extended to the analysis of real samples and concentration of herbicides at 0 day in soil samples varied from 0.483 ± 1.65 to 1.420 ± 1.41 µg g −1 . At harvest, the concentrations of herbicides in soil and rice were below the permissible limit (<0.01 µg g −1 ).